Country Partnership Framework for Poland for the Period of FY19-24 - World Bank Group (World Bank, Washington, DC, 2018)
Poland has reached high-income status over a relatively short period of time, an experience with potential lessons for other countries. However, Poland's development path still faces vulnerabilities and to consolidate gains and address the complex challenges of the future will require strong institutions. The recent Systematic Country Diagnostic (SCD) assesses Poland's most critical institutional constraints and identifies priorities where targeted support could further boost shared prosperity in a sustainable manner. Given Poland's achievements, but also its remaining institutional challenges, this Country Partnership Framework (CPF) makes a marked departure from previous World Bank Group (WBG) engagements. The design of the CPF results framework is based on the SCD's institutional assessment and is fully consistent with the government's strategy for responsible development that places people at the center of its development agenda. This CPF program has six specific objectives in three focus areas: i) Human capital investments and entrepreneurship for the twenty first century; ii) strong institutions for shared prosperity; and iii) resilience to environmental and global risks. The CPF will cover a six-year period (FY19-24) with Progress and Learning Reviews (PLR) planned for every two to three years.